Functional anatomy of the syrinx of the chukar partridge (Galliformes: Alectoris chukar) as a model for phonation research - Erdogan, Serkan; Sagsoz, Hakan; Paulsen, Friedrich (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2015)
The phonation process of vertebrates is influenced by the material characteristics of the participating structures, ranging from molecular to macroscopic dimensions. Good animal models for phonation research are still lacking. Due to easy availability and relatively simple structure, the syrinx of birds might serve as a good animal model for this purpose. Our aim was therefore to determine structural features of the syrinx and obtain insights into its mucus layer characteristics. Epithelium and glands were analyzed using histological, histochemical, and immunohistochemical methods and conclusions were drawn on the use of the syrinx as a model for phonation research by comparing the epithelium and its mucus characteristics to human laryngeal secretions. Ten adult partridges were analyzed. The tympanum of the syrinx developed from the last two tracheal cartilages, whereas the caudal part of the syrinx was formed from eight pieces of bronchial cartilages. The tracheal and bronchial epithelia and the pessulus of the syrinx were lined by pseudo-stratified columnar epithelium in which goblet cells and intraepithelial glands were localized. Collagen fibers were distributed in the lamina propria of all parts of the syringeal mucosa. Elastic fibers in the membranes of the syrinx showed evident distribution. All glandular epithelial cells and goblet cells were positive for neutral, acidic and carboxylated mucins were dominant in particular. Epithelium and glands revealed positive reactivity with antibodies to the mucins MUC1, MUC2, and MUC5AC. Of these, MUC2 and MUC5AC were dominant. The syrinx of partridge can serve as a good ex vivo model for phonation research.
EVALuna2:4440